Pengaruh Risiko Perusahaan, Fungsi Audit Internal, Independensi Dewan Komisaris Terhadap Fee Audit - Daffa Raiza Herlambang; Annisa Nurbaiti (Owner : Riset dan Jurnal Akuntansi, 2023)
The auditor will charge the audited firm a fee, called the "audit fee," in exchange for doing the audit. the fee charged by the auditor for conducting an audit is impacted by diverse aspects like the intricacy of the assignment, the expertise required to carry it out, the fee structure of the knowledge acquisition program (KAP) and other pertinent professional elements. the objective of this inquiry is to recognize the influence in audit fees on banking sub sector on the indonesia stock exchange between 2017 and 2021 in relation to corporate risk, the internal audit function, independence of the board of commissioners. the population comprises of orporations sub sector banking and indexed at the indonesia stock exchange at some point of the duration spanning from 2017 to 2021. in this research, a purposive selection technique was utilized. twenty company, and data from 100 units on the banking sub sector registered on the indonesia stock exchange were utilized for the sample. quantitative methods were employed for the analysis. the analysis in this paper is conducted through the utilization of eviews 12 software is used for the analysis in this paper. based on the results of this study, it shows that the company's risk. the internal audit function, and the independence of the board of commissioners simultaneously affect the audit fee. while the results of the partial test of company risk and the independence of the board of commissioners have no effect on the audit fee, while the internal audit function has an effect on the audit fee.